2008
DOI: 10.1080/15017410801900390
|View full text |Cite
|
Sign up to set email alerts
|

Video Observations of Dyadic Interaction: Behaviour style of Presymbolic Children

Abstract: Research has shown that the behaviour style of children with multiple disabilities who do not use symbols in their communication affects their interaction with others. This study investigated the patterns of caregiverÁchild interaction and the relation between patterns of interaction and behaviour style in seven children with multiple disabilities who do not use symbols. Purposive sampling was employed and video recordings of caregiverÁchild interaction were performed during home visits. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Using visual methods, such as video recordings, in combination with other forms of data collection can elicit deep insights from participants and ensure clarity in questions and response, for example ( Glegg, 2019 ). In the research context of childhood disability, Wilder (2008) reported that using video recordings of everyday interactions when interviewing parents complemented other research methods and added greater depth to the data material. Activity settings are the core unit of analysis for ecocultural theory and comprise five components.…”
Section: Methodsmentioning
confidence: 99%
“…Using visual methods, such as video recordings, in combination with other forms of data collection can elicit deep insights from participants and ensure clarity in questions and response, for example ( Glegg, 2019 ). In the research context of childhood disability, Wilder (2008) reported that using video recordings of everyday interactions when interviewing parents complemented other research methods and added greater depth to the data material. Activity settings are the core unit of analysis for ecocultural theory and comprise five components.…”
Section: Methodsmentioning
confidence: 99%
“…Research findings have indicated that interactions with others are highly important for quality of life (Petry et al 2005), in particular, sensitive contingent responding by interaction partners (Forster and Iacono 2008). Parents have been found to be very aware of their child's communication style, using this to maintain interaction (Wilder 2008) and consistent behavioural repertoires by people with PMLD can be interpreted by communicative partners as conveying affective states (Petry and Maes 2006). Despite this, evidence suggests that staff do not adjust their language to meet the needs of people with intellectual disability (Healy and Noonan Walsh 2007) though they reported that it was important to do so.…”
Section: Communicationmentioning
confidence: 99%
“…2009) and at evaluating (e.g. Healy & Noonan Walsh 2007; Wilder 2008b) or improving (e.g. Granlund & Olsson 1999; Bloomberg et al .…”
mentioning
confidence: 99%
“…Although the dialogical viewpoint appears to be highly advantageous for approaching communication with persons with PIMD, it has seldom been adopted as an explicit starting point for research. In the few papers using the viewpoint, Olsson (2004) provided a detailed qualitative description of the co‐regulation between a child with PIMD and his caregiver, and Wilder (2008b) studied the dynamics of turn taking in interactions with children with PIMD. However, no specific studies reporting on dialogue between persons with PIMD and their communication partners are available.…”
mentioning
confidence: 99%